Technological Capital Mediation on the Effect of Digital Marketing in Increasing Msme Sales in Batola Regency - Hikmahwati Hikmahwati; Widya Ais Sahla (Ilomata International Journal of Social Science, 2022)
The digital era for MSMEs is a new era that is full of challenges but has big opportunities. Challenges and opportunities can be used as a strength by MSMEs to face the economic crisis after the Covid-19 pandemic. The impact of the Covid-19 pandemic on MSME actors has caused sales to drop drastically, this is also felt by MSMEs in Barito Kuala Regency. So it is necessary to have a marketing strategy to increase the number of sales by utilizing digital technology. The purpose of this study was to determine the direct and indirect effect of digital marketing in increasing sales of MSMEs in Barito Kuala Regency with the mediation of technological capital. It is hoped that this research will serve as a solution for MSMEs in Barito Kuala Regency in increasing and recovering sales after the Covid-19 pandemic. This study uses a descriptive quantitative approach. The sample in this study amounted to 93 MSME actors around Barito Kuala Regency which were taken randomly. The analysis used in this study is Path Analysis and the Sobel test (Sobel-test) for testing the intervening variables. The results of the study show that digital marketing has a direct or indirect effect and technological capital is an intervening variable that can mediate the influence of digital marketing on increasing sales of MSME actors in Batola Regency.